The relationship between volunteers satisfaction and intention to continue volunteering in community running events / Azlina Zid …[et al.] - Zid, Azlina; Mazlan Hanafi, Adlin Hani; Wahab, Siti Aishah; Muhammad Rafiai, Nurul Ain; Mohd Nor, Maizan; Samat, Hajar Asmidar; Amiruddin, Rozita (Universiti Teknologi MARA, 2021)
This purpose of this study is to identify the relationship between volunteers’ satisfaction and intention to continue volunteering as a volunteer in the future. There were 133 volunteers from MY10K Night run involved in this community-running event. Volunteer’ satisfaction and intention to continue volunteering questionnaires were used in this study. The data was analysed using descriptive and inferential statistics to identify the percentage, mean, standard deviation and pearson correlation. The study findings showed that there was a significant relationship between the volunteers’ satisfaction and the intention to continue volunteering (r=0.37, p<0.01 . The nature of work (m=4.10) was the highest factor of volunteers’ satisfaction to remain as volunteers in future events and followed by appreciation (m=4.01). Whereas supervision and communication (m=3.96) were found to be least volunteers’ satisfaction to remain as volunteers. Identifying these factors of volunteering, as well as the relations between them, can be beneficial for the management of volunteers to retain the experienced volunteers and to ensure the continuation of the event in the future.